Pengaruh Penggunaan Media Pembelajaran Flipchart terhadap Hasil Belajar Kognitif Siswa Kelas X SMA Negeri 24 Maluku Tengah : (The Effect of Using Flipchart Learning Media on Cognitive Learning Outcomes of Class X Students of SMA Negeri 24 Maluku Tengah) - Talakua, Calvin; Aloatuan, Febiayu (BIODIK, 2021)
The accuracy of using the media indirectly will stimulate students to take part in these lessons so that it will affect the good and bad results of student learning. The research design used Two Group Randomized Subjeck Posttest Only, by selecting two classes, namely the experimental class group and the control class group. The experimental class group used Flipchart learning media while the control class used conventional learning models. The same test was given to both classes, namely at the end of the lesson (posttest). From the results obtained, it is known that the cognitive learning outcomes of students using flipchart learning media are much better than students who use conventional learning models. This can be seen from the average score of the experimental class which is much higher than the control class, which is 80.44, while the control class is 58.93. From the results of hypothesis testing, it shows that tcount = 4.26 and ttable = 1.67 at the significant level Î± = 0.05 with degrees of freedom dk = (34+ 34-2). Based on the criteria for the hypothesis accept H0 if tcount <ttable with degrees of freedom dk = (n_1 + n_ (2) - 2) with a significant level Î± = 5% for other t values â€‹â€‹H0 is rejected. Judging from the results of the calculation, it is known that the value of tcount> ttable. So that H_ (0) is rejected and H1 is accepted, which means that there is an effect of Flipchart learning media on cognitive learning outcomes of class X students of SMA Negeri 24 Maluku Tengah. Abstrak. Ketepatan penggunaan media secara tidak langsung akan menimbulkan rangsangan dari diri siswa untuk mengikuti pelajaran tersebut sehingga akan mempengaruhi baik buruknya hasil belajar siswa. DesainÂ penelitianÂ iniÂ menggunakan Two Group RandomizedÂ Subjeck Posttest Only, denganÂ memilihÂ duaÂ kelasÂ yaituÂ kelompokÂ kelasÂ eksperimen dan kelompokÂ kelasÂ kontrol.Â KelompokÂ kelasÂ eksperimenÂ menggunakanÂ media pembelajaran FlipchartÂ sedangkanÂ kelasÂ kontrolÂ menggunakanÂ modelÂ pembelajaranÂ konvensional. TesÂ yangÂ samaÂ diberikanÂ padaÂ keduaÂ kelasÂ yaituÂ padaÂ akhirÂ pembelajaran ( postes). DariÂ hasilÂ yang didapatÂ diketahui hasil belajar kognitif siswaÂ yangÂ menggunakanÂ media pembelajaran Flipchart jauhÂ lebihÂ baikÂ daripadaÂ siswaÂ yangÂ menggunakanÂ modelÂ pembelajaranÂ konvensional.Â HalÂ iniÂ dilihatÂ dariÂ rata-rataÂ skorÂ kelasÂ eksperimenÂ yangÂ jauhÂ lebihÂ tinggiÂ dariÂ kelasÂ kontrolÂ yaituÂ 80.44Â sedangkanÂ kelasÂ kontrolÂ 58,93. DariÂ hasilÂ pengujianÂ hipotesisÂ menunjukanÂ bahwaÂ thitung Â Â = 4.26 Â ttabelÂ =Â 1.67Â padaÂ tarafÂ singnifikanÂ Â =Â 0,05Â denganÂ derajatÂ kebebasanÂ dk = (34+ 34 - 2 ).Â BerdasarkanÂ kriteriaÂ hipotesis Â terimaÂ Â H0 jika Â thitung < ttabel Â denganÂ derajatÂ kebebasanÂ dk = ( Â + - 2 )Â denganÂ tarafÂ signifikanÂ Â = 5% untukÂ nilai tÂ lainnyaÂ H0Â ditolak.Â DilihatÂ dariÂ hasilÂ perhitunganÂ yangÂ didapatÂ diketahuiÂ nilaiÂ thitung Â ttabelÂ SehinggaÂ Â Â demikianÂ ditolakÂ danÂ H1Â diterimaÂ yangÂ Â Â artinyaÂ bahwaÂ adaÂ pengaruhÂ media pembelajaran Flipchart terhadapÂ hasil belajar kognitif siswa kleas X SMA Negeri 24 Maluku Tengah.Â